Reel Gardening : making a profit to fight poverty - Truscott, Ashley; Urban, Boris; Venter, Robert ([London] : SAGE, 2016)
During 2013, Claire Reid, founder and director of Reel Gardening, a manufacturer of prefertilised vegetable and herb seed strips, met with Emily Jones, head of Reel Life, the community-focused arm of Reel Gardening. Reel Life aimed to address food security in South Africa by helping low-income communities plant food gardens using Reel Gardening's products. Reid was concerned that Reel Gardening was not making the profits it needed to fund the growth she envisaged for Reel Life. This book examines how Reid and Jones set about growing Reel Gardening so that Reel Life could have its maximum impact.
Originally Published in: Truscott, A., Urban, B., & Venter, R. (2014). Reel Gardening: Making a Profit to Fight Poverty. WBS-2014-02. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Reel Gardening (Firm); Entrepreneurship -- Case studies; New business enterprises -- Case studies; Social entrepreneurship -- Case studies